Effectiveness of an oral hygiene promoting program for elementary school students using a smartphone endomicroscope in Thailand - Jintana Sarayuthpitak; Sarinya Rodpipat; Sanong Ekgasit; Dean M. Ravizza (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - The purpose of this paper is to examine the effectiveness of oral hygiene promoting program (OHPP) using a smartphone endomicroscope among students in elementary schools in Bangkok, Thailand, to enable their oral hygiene maintenance and to compare oral health outcomes in the intervention program between the experimental and control groups. Design/methodology/approach - This is a quasi-experimental research study consisting of two groups, a pretest, a posttest and a follow-up design. The student sample consisted of 59 fifth graders who matched the study criteria on medium and low levels of teeth brushing skills. There were 29 experimental group participants who completed the six-week OHPP using a smartphone endomicroscope. Another 30 participants formed the control group involved in the ordinary oral health education program. The comparison data for oral health behaviors (knowledge, attitude and practice (KAP)) and oral hygiene were statistically analyzed by using multivariate analysis of variance (MANOVA). Findings - Results indicated that the experimental group exhibited higher oral health behaviors regarding KAPs and oral hygiene related to teeth cleanliness and gum health than the control group in the postexperimental and follow-up phases. However, there were no statistically significant differences between the two groups with regard to tongue cleanliness. Originality/value - The students maintain their own oral hygiene due to a provision of activities related to KAP concerns. The instrument helped the students to find tooth decay and dental plaque associated with teeth cleanliness after brushing their teeth.